Cost Analysis and Waste Elimination in Efforts to Prepare Inpatient Room Rates as an Efficiency and Effectiveness Strategy in Managing a Hospital Business - Budhi Setianto; Aan Adriansyah, Agus; Asih, Akas Yekti Pulih (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
ABC Hospital is a class B hospital with an increase in capacity to 238 beds. The process of cost analysis and unit cost preparation is very necessary in determining the burden of each service unit. This calculation is used to prepare service rates, in this case the inpatient room rates. The aim of this research is to analyze BPJS inpatient costs, analyze financial costs during January – July 2023, compare costs with predetermined plans and calculate fixed costs, variable costs and semi-variable costs in calculating inpatient rates. This research is descriptive qualitative, by processing secondary data that has been provided. The data used is service visit data from medical records, financial data for January – July 2023, BPJS TXT data for January – July 2023. ABC Hospital has carried out controls related to quality control and costs, by prioritizing effectiveness and costs. The biggest income is from BPJS income while the biggest cost is labor costs. In calculating unit costs, several cost variables are used, including Fixed Cost, Semi-variable Cost and Variable Cost with the average unit cost being 362,020 rupiah. Keywords: Income, Expense costs, Unit Cost, Tariff